Eficacia de la prueba rápida para helicobacter pylori en pacientes con gastritis y/o úlcera gástrica - Huertas De Los Santos, Humberto (2010)
A descriptive study was realized - correlacional in an alone group in the Hospital Bethlehem of Trujillo between October, 2007 to October, 2008 in order to determine the efficiency of the rapid test to detect Helicobacter pylori in patients with diagnosis of gastritis and / or gastric sore The sample belonged 87 patients who were realized endoscopía by gastric biopsy and also the rapid test in blood, to detect Helicobacter pylori with the test Acon Laboratories Inc., the results were analyzed by the test Z of difference of proportions and finally the Index of Validity was established. Results: Helicobacter pylori was detected in 51.7 % of patients by means of the gastric biopsy and 62.1 % by the rapid test in blood, by significant difference. The index of validity was 89.7 %. Conclusion: Applies only to the present study, the rapid test in blood to detect Helicobacter pyloricon, in patients with diagnosis of gastritis and / or gastric sore in the Hospital Bethlehem of Trujillo is effective in 89.7 % taking the findings as a reference histopatológicos and microbiological of the gastric biopsy. This conclusion should take into account only for the screening of detection of this agent.